Pendampingan Pencegahan Covid 19 Melalui Protokol Kesehatan Di Pondok Pesanrten Darussalam Sumbersari - Dzulfikar Zaki; Wildan Habibi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
This research is in the background of massive conducted by Pondok pesantren Darussalam Sumbersari to Santri-santrinya since the COVID 19 outbreak last December. COVID-19 virus that can be transmitted from person to person can even attack anyone who does not know people, both from old, young and even children, a clean and healthy lifestyle is the best solution in anticipation of early transmission of the virus in santri-santrinya. Pondok pesantren Darussalam Sumbersari emphasizes to Santri-santrinya to always behave in a healthy and clean life through various ways, one of which is washing hands. This study aims to find out how to apply to santri-santri as an early prevention effort for COVID 19. The method used in this reset is action research. Based on the results of research santri-santri Pondok Pesantren Darussalam Sumbersari is very enthusiastic to implement as an effort to prevent Covid-19 by washing hands with soap, maintaining environmental cleanliness, eating nutritious food and others.